2019
DOI: 10.3390/ijerph17010262
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Subjective Well-Being through Physical Activity for the Elderly in Korea: A Meta-Analysis Approach

Abstract: The purpose of the current study was to meta-analytically investigate the psychological impacts of physical activity for the elderly population in Korea. The findings from 21 studies, using the comprehensive meta-analysis (CMA) program, indicated that participation in physical activity had a low, but meaningful, impact on the subjective well-being of elderly individuals. Of three exercise dose components, the duration of physical activity was the most influential, followed by the frequency and intensity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 18 publications
4
20
0
Order By: Relevance
“…People are no longer satisfied with experiencing short-term, monotonous rewards; instead, they prefer pursuing the long-lasting and multidimensional benefits achieved as they progress in leisure participation ( Zhou et al, 2017 ). Previous literatures documented the benefits of leisure-time physical activity (LTPA) among working adults, clinical populations, deprived communities, children, and older people ( Guicciardi et al, 2019 ; Paggi et al, 2016 ; Wiese et al, 2018 ; Won et al, 2020 ). Under such circumstances, LTPA has rapidly become one of the top choices among many different groups of people pursuing a healthy life.…”
Section: Introductionmentioning
confidence: 99%
“…People are no longer satisfied with experiencing short-term, monotonous rewards; instead, they prefer pursuing the long-lasting and multidimensional benefits achieved as they progress in leisure participation ( Zhou et al, 2017 ). Previous literatures documented the benefits of leisure-time physical activity (LTPA) among working adults, clinical populations, deprived communities, children, and older people ( Guicciardi et al, 2019 ; Paggi et al, 2016 ; Wiese et al, 2018 ; Won et al, 2020 ). Under such circumstances, LTPA has rapidly become one of the top choices among many different groups of people pursuing a healthy life.…”
Section: Introductionmentioning
confidence: 99%
“…Also, for older adults with poor mobility, the WHO recommends 3 days or more per week of physical activity to enhance balance and prevent falls. However, the physical activity practice rate of the older adults in Korea is low, not even reaching 50% of the target [ 16 ]. In addition, Koreans have exceeded the Organization for Economic Cooperation and Development (OECD) average life expectancy, and the life expectancy of Korean females is 85.4 years [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Productive time-use means active lifestyle and involvement in various activities, such as physical exercise, hobbies, social, and leisure activities. Past studies have shown that practicing an active lifestyle by participating in physical activity and social activities are associated with better cognitive function [ 8 , 9 ], higher wellbeing [ 10 , 11 ], and lower depressive symptoms [ 12 , 13 ] in older adults.…”
Section: Introductionmentioning
confidence: 99%